2009
DOI: 10.1080/00498250802687657
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofSchisandra chinensisextract andGinkgo bilobaextract on the pharmacokinetics of talinolol in healthy volunteers

Abstract: The authors investigated the effect of herbal medicine Schisandra chinensis extract (SchE) and Ginkgo biloba extract (GBE) on the oral pharmacokinetics of P-glycoprotein substrate talinolol in humans. Twelve healthy male volunteers took a single 100-mg oral dose of talinolol either alone or after pretreatment with 300 mg SchE twice daily or with 120 mg GBE three times daily for 14 days. On day 14, a single 100-mg oral dose of talinolol was administered. Plasma concentrations of talinolol from zero to 24 h were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Schizandraceae) is used in modern Chinese medicine as an adaptogenic drug [137]. A clinical trial showed that the herb increased the area under the curve and T max of tanilolol, a P-glycoprotein substrate [82]. Thus, patients receiving S. chinensis might require dose adjustments when treated with drugs primarily transported by P-glycoprotein.…”
Section: Clinical Interactions Between Herbs and Conventional Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schizandraceae) is used in modern Chinese medicine as an adaptogenic drug [137]. A clinical trial showed that the herb increased the area under the curve and T max of tanilolol, a P-glycoprotein substrate [82]. Thus, patients receiving S. chinensis might require dose adjustments when treated with drugs primarily transported by P-glycoprotein.…”
Section: Clinical Interactions Between Herbs and Conventional Drugsmentioning
confidence: 99%
“…Ginkgoaceae) are used for the treatment of cognitive impairments, dementia, intermittent claudication and tinnitus [2,3,4,5]. The effect of ginkgo on various CYP isoforms as well as on P-glycoprotein has been investigated in a number of clinical trials by using different probe drugs, such as alprazolam, midazolam, diazepam, nifedipine (CYP3A4), caffeine (CYP1A2), chlorzoxazone (CYP2E1), debrisoquine (CYP2D6), tolbutamide, diclofenac, flurbiprofen (CYP2C), omeprazole, voriconazole (CYP2C19), fexofenadine, digoxin and talinolol (P-glycoprotein substrates) [55,56,72,73,74,75,76,77,78,79,80,81,82]. Given the heterogeneity of the results, firm conclusions cannot be drawn.…”
Section: Clinical Interactions Between Herbs and Conventional Drugsmentioning
confidence: 99%
“…In addition, several clinical studies observed herb drug interactions between Ginkgo biloba extract and conventional medicinals used in early diabetic nephropathy, such as tolbutamide [57, 58], talinolol [59, 60], metformin [61], nifedipine [62], and atorvastatin [63]. It was reported that combined use of Ginkgo biloba extract with tolbutamide [57] or talinolol [59] might affect their efficacy at higher doses (between 320 mg daily and 360 mg daily, resp.).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that combined use of Ginkgo biloba extract with tolbutamide [57] or talinolol [59] might affect their efficacy at higher doses (between 320 mg daily and 360 mg daily, resp.). In this review, no study reported herb drug interaction caused by Ginkgo biloba extract.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Panax Ginseng was monarch drug, Ophiopogon Japonicus was minister drug, and Schisandra Chinensis acted as the role of assistant and messenger drug. According to previous reports, several kinds of Schisandra lignans were found can alter pharmacokinetics of substrates of P-gp [17][19]. In recent years, several publications have already discussed the relationship between ginsenosides and P-gp [20][25], and most of the studies are carried based on the single component of Ginsenosides Extract .…”
Section: Introductionmentioning
confidence: 99%